2021
DOI: 10.3390/su13116419
|View full text |Cite
|
Sign up to set email alerts
|

Regional Comparison and Strategy Recommendations of Industrial Hemp in China Based on a SWOT Analysis

Abstract: The hemp (Cannabis sativa L.) industry has great potential growth due to its multifaceted characteristics, however, challenged by the imbalance between the rapid agricultural production growth and the inadequate market. Against the manifesting functional overlapping and homogeneous competition among regions and nations, multi-regional synergistic development strategies of the hemp industry are critical for a sustainable agricultural-industrial system. To propose development strategies and R&D priorities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In 2019, an estimated 76,730 tons of hempseed were harvested worldwide from 2.3 × 10 4 hectares, and the crop was valued at over $126 million (US), and an estimated 174 million tons of hemp tow and waste was produced on 6.9 × 10 4 ha (FAOSTAT, 2019). Leaders in acreage of C. sativa are the United States, China, and Canada, but strict government regulations are imposed on production in each of these countries (Mark et al, 2020;Pusiak et al, 2021;Zhao et al, 2021). China produced an estimated 7.14 × 10 4 tons of hempseed on 1.26 × 10 4 ha in 2019 (FAOSTAT, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, an estimated 76,730 tons of hempseed were harvested worldwide from 2.3 × 10 4 hectares, and the crop was valued at over $126 million (US), and an estimated 174 million tons of hemp tow and waste was produced on 6.9 × 10 4 ha (FAOSTAT, 2019). Leaders in acreage of C. sativa are the United States, China, and Canada, but strict government regulations are imposed on production in each of these countries (Mark et al, 2020;Pusiak et al, 2021;Zhao et al, 2021). China produced an estimated 7.14 × 10 4 tons of hempseed on 1.26 × 10 4 ha in 2019 (FAOSTAT, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…China produced an estimated 7.14 × 10 4 tons of hempseed on 1.26 × 10 4 ha in 2019 (FAOSTAT, 2019). Zhao et al (2021) reported that acreage in the FAO database was under-reported and that actual acreage was 6.54 × 10 4 ha in 2020. In the United States, sales in 2020 were $17.5 billion, a 46% increase from 2019 (Yakowicz, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the mechanisms of this plant’s tolerance to drought stress is essential, as drought is one of the most fundamental problems to which Cannabis cultivation is exposed. For example, as one of the largest growers of hemp, China is facing increasing water scarcity, reflected in the reduction of production and quality of hemp materials [ 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biggest hemp ber manufacturer countries, according to 2018 data, are ranked as China, South Korea and the Netherlands. The mean world hemp ber production of 2018 was 60.000 tonnes [19].…”
Section: Introductionmentioning
confidence: 99%